2022
DOI: 10.1155/2022/8609590
|View full text |Cite
|
Sign up to set email alerts
|

Roles Played by the PI3K/Akt/HIF-1α Pathway and IL-17A in the Chinese Subtype of Chronic Sinusitis with Nasal Polyps

Abstract: Background. The Chinese subtype of CRSwNP may have a unique pathogenesis. This study was designed to seek the role of the PI3K/Akt/HIF-1α pathway and IL-17A in CRSwNP. Methods. The total IgE, ECP, and IL-17A levels were determined by UniCAP100 and ELISA. The activity of MPO was detected by the biochemical techniques. The protein expressions of HIF-1α, p-Akt, and PI3K were detected by the WB method. HIF-1α and IL-17A mRNA levels were measured by RT-PCR. Results. The CRSwNP group showed significantly elevated MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Cheng et al reported higher levels of p-Akt and PI3K protein expression in NP tissues obtained from patients with both NPs and CRS compared to control tissues. They suggested that the PI3K/Akt pathway may be involved in the pathogenesis of CRS and NPs, and it may be used as a therapeutic target for the treatment of many diseases 30 . Diminished Lrig1 expression via RNA interference may lead to incorrect responses to glioma cells via EGFR and protein kinase B (AKT) activation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al reported higher levels of p-Akt and PI3K protein expression in NP tissues obtained from patients with both NPs and CRS compared to control tissues. They suggested that the PI3K/Akt pathway may be involved in the pathogenesis of CRS and NPs, and it may be used as a therapeutic target for the treatment of many diseases 30 . Diminished Lrig1 expression via RNA interference may lead to incorrect responses to glioma cells via EGFR and protein kinase B (AKT) activation 31 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is involved in autoimmune inflammation processes and allergic reactions [65]. This signalling pathway mainly produces a neutrophil recruitment, and according to the study by Cheng et al [66], NPDF, upon stimulation by TNF-α, are able to produce increased levels of IL-17A via the PI3K/Akt pathway, thus indicating that NPDF may participate in some way in the T3 inflammatory pathway by recruiting neutrophils in cases of CRSwNP without eosinophilia. In addition to the ability to secrete IL-17A, this cytokine can also activate NPDF to produce IL-8 and CXCL1.…”
Section: Interleukin-17 (Il-17)mentioning
confidence: 99%
“…However, upon application of Wortmannin (a selective PI3K inhibitor), these indicators decreased significantly. This suggests that the PI3K/Akt/HIF-1α pathway may regulate IL-17A-related inflammation in CRSwNP ( Cheng et al, 2022 ).…”
Section: Autophagy In Cellular Experiments and Animal Modelsmentioning
confidence: 99%
“…The levels of p-Akt and PI3K proteins were significantly higher in NPs compared to nasal tissues from sinus cyst patients, indicating a potential downregulation of autophagy in CRSwNP patients. Additionally, increased myeloperoxidase (MPO) activity, mRNA levels of hypoxia-inducible factor-1α (HIF-1α), and IL-17A in NPs suggest a link between hypoxia-induced neutrophil inflammation and inadequate autophagy ( Cheng et al, 2022 ). Wang et al (2022) ’s study comparing various protein markers in different CRSwNP groups revealed an activated Akt-mTOR pathway and decreased levels of beclin-1 and LC3II in CRSwNP patients, with no significant differences between eCRSwNP and non-eCRSwNP groups.…”
Section: Autophagy Phenomenon In Tissues Of Crs Patientsmentioning
confidence: 99%
See 1 more Smart Citation